Cointegration Relationships to Estimate the Marginal Cost of Deficit in Planning a Hydrothermal System: The Case of Brazil - Carpio, Lucio Guido Tapia (International Journal of Energy Economics and Policy, 2014)
The aim of this study is to analyze the behavior of gross domestic product (GDP) compared to electricity consumption in Brazil to estimate the curve of deficit marginal cost. The deficit cost is used as exogenous parameter in the chain of models for planning the operation and expansion of a hydrothermal system as part of the total cost of operation. The results show a cointegration relationship between GDP and electricity consumption; therefore, there is a long-term equilibrium relationship between GDP and electricity consumption. This relationship is used to estimate the curve of deficit marginal cost. The possible short-term imbalance can be mitigated using the vector error correction model (VEC). Keywords: Energy deficit; Cointegration; Rationing; Energy planning JEL Classifications: Q40; Q43; Q47; Q48